Conciliating conservation and development in an Amazonian Biosphere Reserve, Ecuador ? - Muñoz Barriga, Andrea (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
Biosphere reserves are protected areas with extraordinary natural and cultural values, conceived as places for reconciliation between conservation and development. The Sumaco Biosphere Reserve (SBR), located in the Northern Ecuadorian Amazon basin is the home of local indigenous communities which have lived in this area for centuries carrying out different subsistence activities (e.g. shifting cultivation, hunting, fishing, and home gardening). During the past decades, tourism initiatives have been implemented as strategies to promote environmental conservation and socio-economic development. In this research, the principal aspects of the management and governance of tourism was examined, as well as its contribution to biodiversity conservation and development. In-depth semi-structured interviews were used to get qualitative information from the main stakeholders. The study shows that tourism is perceived as an important sustainable alternative to mining, oil extraction and hydroelectric projects, which are currently seen as the main threats to conservation in the area. However, tourism in the Sumaco area also faces some problems, which are related to the lack of adequate management and governance strategies, the worst among them being illegality and informality triggering uncontrolled competition, lowering of prices, and decrease in the quality of services. Altogether, these factors could ultimately lead to the overall decline of the destination. To improve the sustainable development of tourism, more efforts on coordination between different sectors (e.g. environment, mining and oil, and tourism) and levels of governments (local, regional, and national) are needed.